Liquid-based synthesis of nickel- And lanthanum- co-doped strontium titanates for use as anodes in all-ceramic solid oxide fuel cell anodes - Stevenson,GR; Boldrin,P; Brandon,NP (2019)
Nickel- lanthanum- co-doped compositions of strontium titanate have been synthesized and characterized by a scaleable liquid-based synthesis that may offer an alternative to conventional solid-state synthesis. La0.52Sr0.28Ti0.94Ni0.06O3 is synthesized from soluble precursors followed by calcination in air. The materials can be made phase pure at temperatures as low as 1250°C, as highlighted by X-ray diffraction, and nickel exsolves in hydrogen in the same way as solid-state-synthesized materials. The particle size can be varied by calcination temperature and ball milling between 2 µm and 20 µm. The material is then measured electrochemically by electrochemical impedance spectroscopy and 4-point DC conductivity. A reduction in particle size from 20 µm to 9 µm results in a large improvement in impedance response measured.